Analisis Kemampuan Berpikir Kritis Sekolah Menengah Atas: Literatur Review - Jabar, Muhamad Barin Abdul; Rasyid, Abdur; Suryaningsih, Yeni (Papanda Journal of Mathematics and Science Research, 2025)
The purpose of this study is to evaluate the critical thinking skills of high school students based on a systematic literature review of a number of studies both nationally and internationally. The approach taken is a literature review, selecting 15 relevant articles published between 2012 and 2024 that measure critical thinking skills using indicators proposed by Facione, Ennis, or similar frameworks. The findings of this study indicate that, in general, high school students' critical thinking skills fall into the low to moderate category, particularly with weaknesses evident in evaluation and inference indicators. Internal factors such as motivation, self-confidence, and metacognitive skills, as well as external factors including learning models, school atmosphere, and the quality of questions posed by teachers, have a significant influence on the achievement of these skills. Active learning methods such as Problem-Based Learning, Argument-Driven Inquiry, STEM-based learning, and the use of Open Educational Resources have proven to effectively enhance critical thinking skills. For future research, it is recommended to test combinations of active learning methods with educational technology and conduct longitudinal studies to monitor the continuous development of these skills.